Evaluation de la qualité de la prise en charge des paludismes au cours de la période de transition de changement de politique au Bénin. - OGOUYEMI-HOUNTO, Aurore (My University, 2011)
The purpose of this retrospective study in 2006 was to evaluate the impact of control activities implemented within the framework of «Roll Back Malaria (RBM) program» on the medical indicators. Study was based on review of the files of children between 0 and 14 years treated in pediatric outpatient or hospital facilities for malaria confirmed by the thick drop smears from January 1, 2001 to December 31, 2005. A total of 1589 files were reviewed. Data was collected using a standardized form. From 2001 to 2005, the number of children treated for uncomplicated malaria seesawed while the number treated for complicated malaria increased. Proper treatment of uncomplicated malaria went from 58.78% in 2001 to 15.38% in 2005. In all study years, quinine was the most-used drug for uncomplicated malaria. Treatment of complicated malaria also improved from 40% in 2001 to 90.61% in 2005. Although malaria-related mortality remained low (< 2%), the death rate increased from 2001 to 2005. Proper treatment of uncomplicated malaria still poses a challenge using quinine indicated in complicated malaria cases. Based on these findings, it appears urgent for the MNCP to intensify training activities at the medical facilities. This is the only means of achieving the strategic goals of « initiative RBM».
Keywords: Roll Back Malaria. Morbidity. Mortality. Malaria